2009
DOI: 10.1111/j.1466-7657.2009.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Migrants' perceptions of using interpreters in health care

Abstract: Using an interpreter was perceived as a hindrance, though also needed in communication with healthcare staff and as a guide in the healthcare system. Face-to-face interaction was preferred, with the interpreter as an aid to communication. As part of individual care planning it is important to use interpreters according to the patients' desires. Healthcare organizations and guidelines for interpreters need to be developed in order for patients to have easy access to highly skilled professional interpreters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
98
6
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 18 publications
16
98
6
7
Order By: Relevance
“…Interpreters did not recommend telephone interpretation because of the lack of body language and the low quality of technical equipment, which is in accordance with previous studies of Arabic-speaking migrants , Bosnian/Croatian/Serbian-speaking migrants (Hadziabdic et al, 2009b) and different kinds of healthcare staff (Hadziabdic et al, 2010). However, the second new finding of this study was that most of the interpreters who were on the agencies' telephone priority lists were employed by agencies who only invest small sums in interpreters' authorisation, training development and opportunities, so many telephone interpreters had low-quality language skills and lacked a professional attitude, which negatively affected communication as well as patient safety and quality of healthcare.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interpreters did not recommend telephone interpretation because of the lack of body language and the low quality of technical equipment, which is in accordance with previous studies of Arabic-speaking migrants , Bosnian/Croatian/Serbian-speaking migrants (Hadziabdic et al, 2009b) and different kinds of healthcare staff (Hadziabdic et al, 2010). However, the second new finding of this study was that most of the interpreters who were on the agencies' telephone priority lists were employed by agencies who only invest small sums in interpreters' authorisation, training development and opportunities, so many telephone interpreters had low-quality language skills and lacked a professional attitude, which negatively affected communication as well as patient safety and quality of healthcare.…”
Section: Discussionsupporting
confidence: 74%
“…and March 2104, by semi-structured interviews and written descriptions. The interview guide and instruction guide for written descriptions were developed based on literature review and experiences described in previous studies of migrants (Hadziabdic et al, 2009a, Hadziabdic and, healthcare staff (Hadziabdic et al, 2010, Hadziabdic et al, 2011 and family members' perceptions and experiences of using interpreters in a healthcare setting (Hadziabdic et al, 2013). Examples of the main interview questions and written instructions are: 1) Please describe the preparation that you do before an interpreting situation in healthcare, and 2) How do you experience your role before, during and after an interpreting situation in healthcare?…”
Section: Designmentioning
confidence: 99%
“…Using professional interpreters was recommended, as they have good knowledge of medical terms and systems and can facilitate effective and productive communication. This phenomenon is not unique to Canada (Hadziabdic et al, 2009(Hadziabdic et al, , 2010(Hadziabdic et al, , 2011. Moreover, studies in the United Kingdom and Sweden have shown that effectiveness of interpretation services is influenced by ethnocultural factors (Hadziabdic et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In Germany, it has been estimated that of 379,848 refugees in need of mental health care in 2015, only 19,472 received treatment (about 5%; BAfF, 2016). In addition, the use of professional interpreters is expensive, and is generally perceived by migrants as hindering their treatment (Hadziabdic, Heikkilä, Albin, & Hjelm, 2009). Using interpreters from the network of the person, such as family members, can be problematic in the context of psychosocial interventions because of confidentiality and issues around potential vicarious traumatization especially when children are asked to be interpreters.…”
Section: Barriers To Mental Health Care For Refugeesmentioning
confidence: 99%